The constitutionalisation of cities and the future of global society. Issue 2 (4th March 2023) - Shaw, Jo; Štiks, Igor
ABSTRACT: The constitutionalisation of cities is analysed as a process through which urban residents operate as constitutionalising forces within their cities through lived experiences, practices and engagement, and cities try to impose themselves as constitutionalising forces within a rapidly transforming global society. This article explores the tensions generated by the constitutionalisation of cities. It focuses on identifying their character, assessing current economic and socio-cultural processes within cities and articulating a vision of the cityscape . Finally, it applies the idea of chronotopes, as developed in literary studies, to the study of cities. This multidisciplinary approach allows us to understand the constitutionalisation of cities, so far as they seek to break into a global society dominated by states and financial capital. It suggests a vision in which acts of urban citizenship may become emancipatory.